Antibody specificities of children living in a malaria endemic area to inhibitory and blocking epitopes on MSP-119 of Plasmodium falciparum (2009)
Merozoite surface protein-119 (MSP-119) specific antibodies which include processing inhibitory, blocking and neutral antibodies have been identified in individuals exposed to Plasmodium falciparum. Here we intend to look at the effect of single and multiple amino acid substitutions of MSP-119 on the recognition by polyclonal antibodies from children living in Igbo-Ora, Nigeria. This would provide us with information on the possibility of eliciting mainly processing inhibitory antibodies with a recombinant MSP-119 vaccine. Blood was collected from children in the rainy season and binding of anti-MSP-119 antibodies to modified mutants of MSP-119 was analysed by ELISA. The MSP-119 mutant proteins with single substitutions at positions 22 (Leu→Arg), 43 (Glu→Leu) and 53 (Asn→Arg) and the MSP-119 mutant protein with multiple substitutions at positions 27 + 31 + 34 + 43 (Glu→Tyr, Leu→Arg, Tyr→Ser, Glu→Leu); which had inhibitory epitopes; had the highest recognition. Children recognised both sets of mutants with different age groups having different recognition levels. The percentage of malaria positive individuals (32–80%) with antibodies that bound to the mutants MSP-119 containing epitopes that recognise only processing inhibitory and not blocking antibodies, were significantly different from those with antibodies that did not bind to these mutants (21–28%). The amino acid substitutions that abolished the binding of blocking antibodies without affecting the binding of inhibitory antibodies are of particular interest in the design of MSP-119 based malaria vaccines. Although these MSP-119 mutants have not been found in natural population, their recognition by polyclonal antibodies from humans naturally infected with malaria is very promising for the future use of MSP-119 mutants in the design of a malaria vaccine.